Urease inhibition and anticancer activity of novel polyfunctional 5,6-dihydropyridine derivatives and their structure-activity relationship - Hameed, Abdul; Anwar, Ayaz; Khan, Khalid Mohammed; Malik, Rizwana; Shahab, Fernaz; Siddiq, Sadia; Basha, Fatima Zahra; Choudhary, Muhammad Iqbal (European Journal of Chemistry, 2013)
A novel series of tricyano substituted polyfunctional 5,6-dihydropyridine 8a-n bearing functionalized aromatic rings at C-4 and C-6 position have been prepared from (α-methylbenzylidene) malononitriles in good to excellent yields (52-98%) in solvent free conditions. All the synthesized compounds (8a-n) were evaluated for their in vitro urease inhibition and anticancer activity against prostate cancer (PC3) and Hela cell lines. Compound 8k (4,6-bis(4-methoxyphenyl)-5,6-dihydropyridin) showed slightly better urease inhibitory potential (IC50 = 20.47 µM) as compared to standard thiourea (IC50 = 21 µM). Whilst in the case of anticancer studies the compound 8a 2-(4,6-bis(4-bromophenyl)-6-methyl-5,6-dihydropyridin found to be most active (IC50 = 4.40 and 8.80 µM) among the series when compared with standard doxorubicin 4 (IC50 = 0.91 and 3.1 µM) in both cell lines respectively. A structure-activity relationship of this series has been established on the basis of electronic effects and position of different substituents (H, Br, Cl, I, F, Me, OMe, OH, and NO2) present on the C-4 and C-6 phenyl rings. The anticancer activity evaluation of these pyridine derivatives envisage that the compound 8a could be putatively linked with doxorubicin IV to developed new anticancer prodrugs for multidrug resistant (MDR) cancer cells. All the synthesized compounds were characterized by spectroscopic techniques.